The Influence of Electronic Word of Mouth (E-Wom) and Brand Awareness on Mixue Purchase Decisions in Medan City - Banjarnahor, Mustika Rotama; Simanjorang, Feronica (Formosa Journal of Applied Sciences, 2024)
This research is aimed at finding the influence/impact of Electronic Word of Mouth (e-WOM) on purchasing decisions, knowing the influence of Brand Awareness on purchasing decisions, and analyzing the combined effect of Electronic Word of Mouth (e-WOM) and Brand Awareness on Mixue purchasing decisions in Medan city. The research method applied is a quantitative method with an associative approach. Samples were taken using a non-probability sampling technique (purposive sampling) by distributing questionnaires to 100 respondents who were students from 10 universities in Medan City. The research results show that together, Electronic Word Of Mouth (X1) and Brand Awareness (X2) have a positive and significant impact on Purchase Decisions (Y) Mixue among Medan City students.